Hak Waris Perempuan dalam Adat Batak Pasca Berlakunya Yurisprudensi MA No. 03/Yur/Pdt/2018 - Novita Sari; Sukri Hidayati (Universitas Sebelas Maret, 2022)
National law is developed and adopted through existing laws in society to ensure that the applicable laws in Indonesia are in accordance with the interests and are intended to accommodate the multicultural conditions of Indonesia. This causes plurality in inheritance law in Indonesia because of the condition of Indonesia which has a variety of cultures. One of the people who live in Indonesia is the Batak community. The Batak community adheres to a patrilineal system. The patrilineal system is a system that still refers to gender differences where the legal heirs are male and female heirs who are only considered as 'enjoyers' of their husband's property. This means that the practice that only boys have the right to become heirs has been going on for generations among the Batak people and women are not entitled to family inheritance. However, with the enactment of Jurisprudence No. 03/Yur/Pdt/2018, this patrilineal practice is threatened with change. This is because the jurisprudence raises the issue of equal rights between men and women. Both are seen as equal in the eyes of the law and have a strong legal standing to claim and obtain inheritance. Therefore, this study aims to determine the inheritance rights of women in Batak customs after the enactment of Jurisprudence No. 03/Yur/Pdt/2018. This research is a descriptive analytical research. The author attempts to describe and provide an overview of the inheritance rights of women in Batak customs after the enactment of Jurisprudence No. 03/Yur/Pdt/2018 by examining the data obtained through literature studies originating from primary, secondary, and tertiary legal sources. The results of this study indicate that customary law in the Batak community has developed towards granting equal rights between girls and boys in relation to being the heirs or successors of the family.